Theoretical Concepts and the Concept of Ethnoculture - Olimkhodzhaevna, Abdullayeva Khafiza (International Journal on Human-Computing Studies, 2023)
The article shows that the process of globalization is rapidly changing the way of life of peoples and nations living in a traditional way.